Clinical Probes and Endogenous Biomarkers as Substrates for Transporter Drug‐Drug Interaction Evaluation: Perspectives From the International Transporter Consortium. Issue 5 (22nd October 2018) - Chu, Xiaoyan; Liao, Mingxiang; Shen, Hong; Yoshida, Kenta; Zur, Arik A.; Arya, Vikram; Galetin, Aleksandra; Giacomini, Kathleen M.; Hanna, Imad; Kusuhara, Hiroyuki; Lai, Yurong; Rodrigues, David; et al.
Abstract : Drug transporters can govern the absorption, distribution, metabolism, and excretion of substrate drugs and endogenous substances. Investigations to examine their potential impact to pharmacokinetic (PK) drug‐drug interactions (DDIs) are an integral part of the risk assessment in drug development. To evaluate a new molecular entity as a potential perpetrator of transporters, use of well characterized and/or clinically relevant probe substrates with good selectivity and sensitivity are critical for robust clinical DDI assessment that could inform DDI management strategy in the product labeling. The availability of endogenous biomarkers to monitor transporter‐mediated DDIs in early phases of clinical investigations would greatly benefit downstream clinical plans. This article reviews the state‐of‐the‐art in transporter clinical probe drugs and emerging biomarkers, including current challenges and limitations, delineates methods and workflows to identify and validate novel endogenous biomarkers to support clinical DDI evaluations, and proposes how these probe drugs or biomarkers could be used in drug development.